Interpersonal dependence and differential types of reflection in students – boys and girls (Law and Safety, 2018)
The article presents results of the study of interpersonal dependence in the context of reflection as a necessary condition for personal autonomy and the mechanism of constructing and organizing a life perspective in adolescence.The psychological content of the phenomenon of interpersonal dependence is revealed, its destructive influence on the personality is emphasized, the positive role of reflection as a factor of actualization of the autonomy of the individual and the neutralization of interpersonal dependence is substantiated.The purpose of the study was to identify the relationship of interpersonal dependence and differential types of reflection in students – boys and girls.The scientific novelty of the research is determined by the fact that in the work for the first time the peculiarities of the functioning of interpersonal dependence and differential types of reflection on the students were determined, differences in the structure of the interrelationship between these phenomena in students – boys and girls were analyzed.The Interpersonal Dependency Inventory by R. M. A. Hirschfeld, Relationship Profile Test by R. F. Bornstein (both – in an adaptation by O. P. Makushina) and Differential Test of Reflexivity by D. A. Leontiev and E. M. Osin were applied to solve empirical problems. The sample consisted of 96 students of V. N. Karazin Kharkiv National University. The first group included of 45 boys, the second – 51 girls. For the mathematical processing of data the Spearman rank correlation coefficient was used.It has been established that in both groups an increase in the propensity to unproductive types of reflection is a potential for the development of manifestations of interpersonal dependence. Both boys and girls, with increased introspection, there is an aggravation of destructive overdependence. It was also found that in young men the increase in such manifestations of interpersonal dependence, such as the need for emotional reliance on others, lack of self-confidence, and dependence in general, occurs along with the actualization of the tendency to introspection, while in girls – with the actualization of the tendency to quasi-reflection, together with than in these subjects, destructive overdependence grows. It should be noted that healthy dependence is involved in relationships with the differential types of reflection only in the group of girls, in which its severity increases with increasing ability to systemic reflection and inhibition of quasi-reflection.Results can be used for gender specification of psychological programs for the prevention and correction of interpersonal dependence in the students age. It is noted that the prospect of further research is to study the psychological characteristics that may act as inhibitors of interpersonal dependence in adolescence.
Keywords: gender; differential types of reflection; interpersonal dependence; personal reflection; autonomy; students